2019
DOI: 10.3233/jad-180780
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Alzheimer’s Disease: An Alternative Role for Selective Serotonin Reuptake Inhibitors?

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 129 publications
0
25
0
2
Order By: Relevance
“… 31 These findings suggest that depressive symptoms may be a prodrome of AD reflecting preclinical disease progression. 32 Evidence for associations of MDD and AD at the clinical and molecular levels also has been reported. 9 Reports have argued that oxidative stress leading to neuronal dysfunction could contribute to the development of both MDD and AD.…”
Section: Discussionmentioning
confidence: 95%
“… 31 These findings suggest that depressive symptoms may be a prodrome of AD reflecting preclinical disease progression. 32 Evidence for associations of MDD and AD at the clinical and molecular levels also has been reported. 9 Reports have argued that oxidative stress leading to neuronal dysfunction could contribute to the development of both MDD and AD.…”
Section: Discussionmentioning
confidence: 95%
“…On top of this, the literature showed that RJ has the potential to improve general mental health of healthy volunteers [ 197 ]. It also documents antidepressant effects of RJ in animal models of depression and anxiety [ 201 , 212 ]. The cellular and molecular mechanisms underlying the action of RJ in animal models of AD and cognitive aging is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients categorized as the most severely agitated actually showed an increase in nighttime behavioral or sleep disruptions when treated with citalopram (Leonpacher et al, 2016). An intriguing body of work also suggests that early administration of SSRIs may also slow the progression of mild cognitive impairment to AD, perhaps through a mechanism by which serotonin affects the amyloid-β precursor protein, thereby reducing the accumulation of amyloid-β (Elsworthy and Aldred, 2019). It is also possible that serotonin's modulation of the circadian system could indirectly play a role in slowing or expediting this progression, as chronic circadian dysfunction exacerbates AD pathology (Musiek, 2015).…”
Section: Serotonergic Inputs To the Circadian Systemmentioning
confidence: 99%